Renal implications of systemic lupus erythematosus pathogenesis and treatment - Taju, Khalid G.; Albusaiteeni, Aysha S.; Allakhmi, Fatima S.; Alawainati, Fatema A.; Alsaie, Maryam R.; Alabdali, Otouf N.; Alanazi, Abdullah K.; Alenezi, Abdullah M.; Alrowithi, Raghad A.; Alkhatlan, Abdullah M.; Osman, Igbal E. (International Journal Of Community Medicine And Public Health, 2025)
Lupus nephritis (LN) is a severe complication of systemic lupus erythematosus (SLE) that significantly contributes to morbidity and mortality. Its pathogenesis involves complex interactions between immune dysregulation, genetic susceptibility, and environmental factors, resulting in immune complex deposition and subsequent renal inflammation. Advances in understanding these mechanisms have highlighted the role of B cells, cytokines, and the complement system in disease progression. Current therapeutic strategies rely on immunosuppressants such as glucocorticoids, cyclophosphamide, and mycophenolate mofetil, which have proven effective in managing renal inflammation but carry risks of significant adverse effects. Biologic agents targeting B cells and complement components, including belimumab and eculizumab, have demonstrated promise in improving outcomes and reducing disease activity in refractory cases. The discovery of novel biomarkers is transforming the diagnosis and management of LN. Urinary markers like MCP-1 and complement activation products offer non-invasive tools for monitoring disease activity and predicting relapses. Molecular studies have identified microRNAs and genetic variants as potential indicators of disease susceptibility and therapeutic response. Advances in metabolomics and proteomics have revealed metabolic and protein profiles unique to LN, offering insights into disease mechanisms and new targets for intervention. Emerging technologies such as artificial intelligence are revolutionizing the analysis of complex biomarker data, enabling personalized treatment approaches. These advances highlight the importance of integrating multidisciplinary research efforts to optimize patient care. While challenges remain, including the heterogeneity of LN and disparities in access to care, ongoing research is paving the way for improved therapeutic options and outcomes. Precision medicine, driven by biomarker discovery and innovative therapies, holds the potential to transform the landscape of LN management, offering hope for better renal preservation and quality of life for affected individuals.